The Use of Capcut Application in Improving Students’ Creativity in Social Studies Learning at Junior High School - Priandini, Dara; Supriatna, Nana; Anggraini, Diana Noor (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
According to 21st Century Skills, creativity is one of the competencies needed in all aspects of life. In addition, the 21st century requires all aspects to be based on technology, especially in education. However, in reality students' creativity skills are still low and the use of technology is still limited. Based on this problem, the purpose of a research in this paper is to describe of students’ creativity skills after using an application Capcut. This research design is classroom action research (CAR). This research result that there was an increase in each cycle. The observation results of the students’ creativity in the first cycle got a percentage 50% which means quite good category, in the second cycle got a percentage 75% which means good category, and in third cycle got a percentage 95% which means good category. Based on this research, it was found that the use of Capcut application can improve students’ creativity skills in social studies learning.